Myosin II is involved in capping and uroid formation in the human pathogen Entamoeba histolytica. - Arhets, P (1995)
The redistribution and capping of surface receptors on the human pathogen Entamoeba histolytica was observed in the presence of concanavalin A (ConA). Capping was correlated with plasma membrane folding towards the rear of the amoeba and with uroid formation. The uroid is thought to play a role in the escape of amoebae from the host immune response. To localize myosin II during capping, amoebae were incubated in the presence of ConA and then analyzed by microscopy. Myosin II was three times more concentrated within the uroid compared with the rest of the cell, suggesting that the release of caps may depend upon mechanical contraction driven by myosin II activity. The use of drugs that disrupt cytoskeletal structure or that inhibit myosin heavy chain phosphorylation demonstrated that inhibition of capping prevents uroid formation. Biochemical analysis allowed the identification of two ConA receptors which have been previously described as major pathogenic antigens of this parasite: the 96-kDa antigen, which carries alcohol dehydrogenase 2 activity and binds extracellular matrix proteins, and the Gal-GalNAc-inhibitable surface lectin, which is involved in amoeba-cell interactions and in the degradation of complement particles attached to the parasite.